2012
DOI: 10.1167/iovs.11-7948
|View full text |Cite
|
Sign up to set email alerts
|

Serum DJ-1/PARK 7 Is a Potential Biomarker of Choroidal Nevi Transformation

Abstract: Elevated serum levels of DJ-1 are associated with choroidal nevi transformation risk factors. Therefore, DJ-1 appears to be a promising factor for predicting the growth of choroidal nevi and may be a potential biomarker of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Its expression is correlated with the transformation and progression of esophageal squamous cell carcinoma. 47 A recent study, Bande et al, 48 finds that elevated serum levels of PARK7 are associated with choroidal nevi transformation risk factors. However, an up-regulation of CAPZA1, PDIA3, SELENBP1, and PARK7 during metastasis, as obtained within our 2D DIGE study, is not reflected in our immunohistochemical analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Its expression is correlated with the transformation and progression of esophageal squamous cell carcinoma. 47 A recent study, Bande et al, 48 finds that elevated serum levels of PARK7 are associated with choroidal nevi transformation risk factors. However, an up-regulation of CAPZA1, PDIA3, SELENBP1, and PARK7 during metastasis, as obtained within our 2D DIGE study, is not reflected in our immunohistochemical analysis.…”
Section: Discussionmentioning
confidence: 98%
“…All the latter factors require tissue sampling, limiting their use in determining the high-risk features of poor prognosis in uveal melanoma. On this basis, Bande et al [45] reported that elevated serum levels of DJ-1 were correlated with known clinical risk factors of nevi growth, and suggested that may be used as a potential biomarker of malignancy. In our study, the mean adiponectin level of the choroidal nevus group (9.2 µg/dl) was found to be lower than the cut-off level of adiponectin determined for uveal melanoma (10.7 µg/dl).…”
Section: Discussionmentioning
confidence: 99%
“…DJ-1 is an oncoprotein secreted by cancer cells, already identified as a potential diagnostic and prognostic biomarker for breast cancer, 9 melanoma, 10 and pancreatic cancer 11 and that, recently, was associated with EC pathogenesis and progression. 12 …”
mentioning
confidence: 99%